Time to dietary diversity of complementary feeding improvements and its associated factors among infants aged 6–12 months in Ethiopia: evidence from performance monitoring for action - Bayisa, Feyisa Shasho; Nimani, Teshome Demis; Darcho, Samuel Demissie; Tekola, Abainash (Frontiers in Nutrition, 2025)
BackgroundInfant and Young Child Feeding significantly affect the health, development, and nutritional status of children under 2 years old, ultimately affecting their survival. The aim of this study is to determine the time to improvement in dietary diversity and associated factors in infants aged 6 to 12 months.MethodsThe study used secondary data from the PMA Ethiopia longitudinal panel survey, involving pregnant women from January to March 2024. The data management and analysis were performed using Stata version 17. The Kaplan–Meier survival curve (KM) and the log-rank test method were implemented. A Cox proportional-hazard regression model was used to explore the association between independent variables and the outcome variable. The strength of the association was indicated by the adjusted hazard ratio (AHR) with a 95% confidence interval. The threshold of p < 0.05 was applied to determine the significance of an association.ResultsThe study found that the proportion of infants with improved dietary diversity aged 6–12 months was 22% (95% CI: 19.5, 25%). Factors associated with improved dietary diversity in infants aged 6 to 12 months were married women (AHR = 9.3, 95% CI = 1.19, 8.30), women with a secondary school (AHR = 1.9, 95% CI = 1.05, 3.51), women with technical and vocational (AHR = 2.0, 95% CI = 1.01, 4.05) and women with a university degree (AHR = 2.9, 95% CI = 1.51, 5.38). Moreover, women in the highest wealth quintile (AHR = 3.5, 95% CI = 1.31, 9.41), women visiting PNC (AHR = 1.7, 95% CI = 1.13, 2.62), women visiting ANC 1–3, and more than four times were (AHR = 2.4, 95% CI = 1.51, 3.74) and (AHR = 3.6, 95% CI = 2.28, 5.67) times higher for improving dietary diversity.ConclusionThe findings of this study showed that the proportion of dietary diversity improvement was 22%. Which is relatively low. Marital status, educational status, wealth index, PNC, and ANC visits were identified as statistically significant factors associated with dietary diversity improvements. It suggests that public health interventions should focus on enhancing maternal knowledge and promoting regular healthcare visits to mitigate malnutrition and improve infant health outcomes in Ethiopia.